Fragmentation in Ancient Greek drama - Lamari, Anna A.; Montanari, Franco, 1950-; Novokhatko, Anna A., 1978- (Trends in classics. Supplementary volumes,, 2020)
This volume examines whether dramatic fragments should be approached as parts of a greater whole or as self-contained entities. It comprises contributions by a broad spectrum of international scholars: by young researchers working on fragmentary drama as well as by well-known experts in this field. The volume explores another kind of fragmentation that seems already to have been embraced by the ancient dramatists: quotations extracted from their context and immersed in a new whole, in which they work both as cohesive unities and detachable entities. Sections of poetic works circulated in antiquity not only as parts of a whole, but also independently, i.e. as component fractions, rather like quotations on facebook today. Fragmentation can thus be seen operating on the level of dissociation, but also on the level of cohesion. The volume investigates interpretive possibilities, quotation contexts, production and reception stages of fragmentary texts, looking into the ways dramatic fragments can either increase the depth of fragmentation or strengthen the intensity of cohesion.